2021
DOI: 10.1016/j.cmi.2020.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response using six different serological assays in a completely PCR-tested community after a coronavirus disease 2019 outbreak—the CoNAN study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 26 publications
2
44
2
1
Order By: Relevance
“…The results of this seroprevalence analysis showed a positivity rate among individuals assisted by the internal healthcare system of the Vatican City State lower than that found in other studies on similar samples ( 7 , 8 , 9 , 10 ). This may be due to the small sample size and to the low number of COVID-19 cases tracked in the Vatican City State thanks to the control and prevention measures taken by the Directorate of Health and Hygiene.…”
contrasting
confidence: 78%
“…The results of this seroprevalence analysis showed a positivity rate among individuals assisted by the internal healthcare system of the Vatican City State lower than that found in other studies on similar samples ( 7 , 8 , 9 , 10 ). This may be due to the small sample size and to the low number of COVID-19 cases tracked in the Vatican City State thanks to the control and prevention measures taken by the Directorate of Health and Hygiene.…”
contrasting
confidence: 78%
“…Positive serologic testing was 1.5 to 8.1 times more likely in people who had had any acute respiratory infection (ARI) symptoms; for the individual symptoms this ranged from 2-fold (fever) to 46-fold (loss of smell and taste). Three studies also reported prevalence of other non-specific symptoms such as headache, chest pain, skin rash, nausea, and fatigue among the participants [ 17 , 24 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The major reason for exclusion was high risk of bias in the selection of participants (Full list of excluded studies in S1 Table ). Seventeen articles-4 preprints, 11 published studies, and 2 government reports-from 15 countries (Argentina, Brazil, Spain, Hungary, Germany, Luxembourg, Switzerland, Denmark, Sweden, Finland, Iceland, the United States of America (USA), the Channel Islands, Iran, and Japan) that tested a combined total of 118,297 participants met eligibility criteria [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. (Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 However, the humoral response to SARS-CoV-2 appears to be proportional to COVID-19 severity: the highest antibody titres are detected in severe and protracted cases, compared with low or undetectable titres in patients with mild or asymptomatic COVID-19. 34 The magnitude of the antibody response often correlates with T-cell responses, although uncoupled responses with strong specific T-cell production and no antibody production have been described. 35 SARS, MERS, and COVID-19 have a similarly short-lived humoral antibody response.…”
Section: Clinical Pathology Of Covid-19mentioning
confidence: 99%